Perfusion index monitoring and its correlation with outcome in neonates undergoing surgery - Ahmad, Sheikh Irshad; Yaseen, Souliha; Wani, Waquar Amin; Yaqoob, Shaista; Bhagat, Neha (International Journal of Contemporary Pediatrics, 2025)
Background: The perfusion index (PI) has been found to be a reliable indicator of peripheral perfusion and can be used to monitor perfusion in neonates undergoing surgical procedures. To study correlation of perfusion index with the need for post op mechanical ventilation, ICU care and inotropic support in neonates undergoing surgery. Methods: Eighty neonates posted for surgery were enrolled after taking proper written informed consent from the parents. HR, BP and SPO2 and PI were recorded at 3 minutes interval for the first 30 minutes of surgery, followed by every 5 minutes till the end of procedure. Neonates requiring admission in the Department of Pediatrics were shifted to the Neonatal ICU or ward. Post-operative vitals were monitored initially every 30 minutes for first 24 hours followed by 2 hourly. Results: There was a statistically significant association between PI and need for post-op mechanical ventilation (MV). Duration of post-operative MV based on PI showed no significant difference. A lower PI was strongly correlated with an increased likelihood of requiring ICU-level care post-operatively, but not the duration of ICU stay. There was a potential association between PI and the requirement for inotropic support. Mortality rate was higher in patients with low PI, but not statistically significant. Conclusions: Low PI in neonates is associated with poor outcome in terms of need for ICU stay, need of postoperative mechanical ventilation and inotropic support.